Exploring the Interplay of Work Engagement and Job Satisfaction in Shaping Employee Performance at the Mentawa Baru Ketapang Sub-District Office - Herliyantie , Herliyantie (JSM: Jurnal Sains Manajemen, 2025)
The Effect of Job Involvement and Job Satisfaction on the Performance of Employees at the Mentawa Baru Ketapang District Office. Thesis Management Department/Study Program, concentration in Human Resource Management, Faculty of Economics and Business. Under the guidance of Prof. Dr. Yunikewaty, MM and Dra. Anike Retawati, MM. This study aims to determine the effect of job involvement (X1) and job satisfaction (X2) on employee performance (Y) in the Mentawa Baru Ketapang District Office. The research method used in this research is quantitative research. The population and sample in this study were employees of the Mentawa Baru Ketapang sub-district office, totaling 31 respondents. The collected data were analyzed using the SPSS (Statistical Product and Service Solution) statistical program, and using the IBS SPSS 26 software.The results of the study show that the work involvement variable has a positive and significant effect on employee performance. Job satisfaction variable has a positive and significant influence on employee performance. And simultaneously work involvement and job satisfaction have a positive and significant effect on employee performance at the Mentawa Baru Ketapang sub-district office.